Population densities of understorey birds across a habitat gradient in Palawan, Philippines: Implications for conservation - Mallari, Neil Aldrin D. (Animo Repository, 2024)
There is widespread concern for many understorey and ground-dwelling bird species in the Philippines that appear intolerant of forest alteration. We present density estimates for 18 key bird species in old growth forest, advanced and early secondary growth and active cultivation within the Puerto Princesa Subterranean River National Park in Palawan. Six species were not recorded in cultivation and the abundance of these and several others increased along the successional gradient from cultivation to old growth forest. Eleven species, including five endemics and three of four threatened species, had highest density estimates in old growth forest. However, several species had high density estimates in the heavily disturbed habitats and every habitat type held highest densities of at least one of the bird species. The commonest habitat association across the bird community was a preference for areas containing large trees, indicating the importance of retention of such trees in allowing suitable ground and understorey microhabitats to persist. Old growth forests have the highest conservation value for Palawan’s endemic birds and, while some species thrive in the anthropogenic habitats that occur within the Park, the present extent of cultivation and associated successional stages within its boundaries should not be increased. We caution against extrapolation of the abundance figures from the Park to the whole island but we suggest that population sizes for the threatened species are likely to be much greater than previously thought. We urge authorities to strengthen management within the protected area network in Palawan to ensure survival of key species.